Simulasi Sebaran Emisi Udara CO dan NH3 Menggunakan AERMOD di TPA Jawa Timur - Rania Ichdatunnisa (Prosiding ESEC, 2023)
The landfill located in East Java produces air emissions in the form of TSP, Hg, CO, NOx and NH3 parameters from the incinerator chimney.. This study aims to test the Aermod model in predicting the distribution of CO and NH3 parameters at landfill in East Java. The quality standards used are listed in Government Regulation no. 22 of 2021 concerning Implementation of Environmental Protection and Management Attachment VII Ambien Air Quality Standards. By using Aermod View Software, dispersion simulation can be calculated. The data used in modeling the distribution of landfill in East Java 2013 – 2022, and Upper Air Met Data in Sidoarjo Regency from 2013 – 2022. So the results obtained are the CO parameter of 12.9 µg/m3, and the NH3 parameter of 0.024 µg/m3.